The Experience of Symbolic Violence among Deaf Students in Disability-Friendly Universities: A Pierre Bourdieu Perspective - Nathacha Nathacha; Moh. Mudzakkir; Wardatul Adawiah; Eufrasia Kartika Hanindraputri (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This research is driven by the contradictory phenomenon at University X, where its status as a